A 10 kHz to 6 GHz Low-Cost Vector Network Analyzer - Depold, Andreas; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (Advances in Radio Science, 2021)

A 9-Channel Phase Coherent Receive System for Direction of Arrival Estimation - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (European Microwave Week 2021, 2022)
Collapsed buildings are a common occurrence after earthquakes, but are also commonly caused by gas explosions. The survival chance of buried victims is heavily dependent on the time it takes to locate and rescue them. This paper introduces a 9-channel phase coherent receive system intended for direction finding in search and rescue applications. The motivation for this system is to minimize the time necessary to locate the buried phones of victims. The design consists of an FPGA based digital system with high speed I/O for data acquisition and signal processing, as well as nine synchronized receivers each covering the entire target bandwidth. A high phase resolution is achieved down to very low input level

A Direction-of-Arrival Estimation System for UAV-Assisted Search and Rescue: Locating Mobile Phones to Improve the Survival Chance of Disaster Victims - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (IEEE Microwave Magazine, 2023)
Collapsing buildings are, while not exactly common, still an issue. The causes are diverse and often region dependent. The most common cause of the large-scale structural failure of buildings is earthquakes. In countries less affected by earthquakes, explosions caused by gas leaks are the leading cause.
CRIS-Team Scopus Importer:2023-03-03

A Light Weight 3x3 Switched Polarity URA Antenna and Receive System for Direction Finding - Depold, Andreas; Dorn, Christian; Erhardt, Stefan; Weigel, Robert; Lurz, Fabian (2022 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2022, 2022)
Minimizing the time it takes to locate and rescue victims from building collapses is critical for their survival chance. This scenario causes a challenging environment for radio frequency based localization. This paper introduces a direction finding system based on a 3x3 uniform rectangular array with integrated polarization switching for multipath mitigation intended for search and rescue applications. It is shown that utilizing two polarizations can be used to reduce or eliminate ambiguities caused by multipath propagation. Further approaches to optimize localization ability are discusse
CRIS-Team Scopus Importer:2022-04-15
Keywords: Antenna arrays; Direction-of-arrival estimation; phase detection; receivers

A Simple Low Jitter Wireless Triggering and Unidirectional Communication System - Depold, Andreas; Dorn, Christian; Weigel, Robert; Lurz, Fabian (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
This paper presents a simple, low-cost synchronization system based on a Sub-GHz of-the-shelf transceiver. It is intended for synchronization between a base station and mobile measurement system for search and rescue applications. Time critical scheduling information can be transmitted together with triggering pulses. Additionally, during off time bulk data can be transmitted. The system allows for triggering with a known latency and with a standard deviation below 200 ns.
Created from Fastlane, Scopus look-up
Keywords: triggering; wireless sensors; wireless synchronization

EuroVNA - ein ambitionierter Netzwerkanalysator - Erhardt, Stefan; Depold, Andreas (2020)

Low-cost Software-Defined Radio System with Deterministic RX to TX Delay Using Timestamps - Dorn, Christian; Depold, Andreas; Lurz, Fabian; Hagelauer, Amelie (2023 IEEE Topical Conference on Wireless Sensors and Sensor Networks, WiSNeT 2023, 2023)
Systems that rely on high-level software share the same disadvantage. Their execution time is unknown and thus the result of the processing is not available after a deterministic delay. The same is valid for software-defined radios. When only in receive (RX) mode the impact of the varying delay is negligible most of the time. However, in the case that the SDR needs to transmit (TX) this delay prevents from synchronizing the TX to the RX. This is crucial for many applications in communication and sensing though. This publication proposes and implements a method on a low-cost SDR transceiver, that provides the possibility to TX at a given time related to the RX with an error of ±l sample.
CRIS-Team Scopus Importer:2023-03-17
Keywords: software-defined radio (SDR); time synchronization

UAV-based Localization of Mobile Phones for Search and Rescue Applications - Dorn, Christian; Depold, Andreas; Lurz, Fabian; Erhardt, Stefan; Hagelauer, Amelie (2022 IEEE 22nd Annual Wireless and Microwave Technology Conference, WAMICON 2022, 2022)
In this work a system is proposed that utilizes an unmanned aerial vehicle (UAV) to search and rescue trapped victims using their mobile phones. The systems consists of two parts, a ground station (GS) and an airborne station (AS). The GS provides a downlink to the UAV, a GSM base station along with antenna equipment and a mobile network jamming device. By using a smart approach to block the synchronization sequences of all base stations in range, the mobile phones of the victims to be located are switching to an emergency fallback mode. In this mode the phones connect to the strongest base station in range, thus the one provided by the GS. By initiating a call to the corresponding phone the AS can localize it using direction-of-arrival detection with a 9-channel phase coherent receiver system.
CRIS-Team Scopus Importer:2022-07-15
Keywords: dar; Jammer; Sar; uav